ANALYSIS OF THE QUALITY OF GREEN OPEN SPACES IN THE OLD TOWN AREA CORRIDOR ON BATANG ARAU STREET, PADANG - Friyessi, Friyessi; Andi, Andi (Journal of Scientech Research and Development, 2025)
The Batang Arau Road Corridor in the Old Town area of Padang, West Sumatra, holds significant historical, ecological, and social value. It is currently facing numerous urban pressures, including tidal flooding and a decline in the quality of green open spaces (green open space). As an area primarily used as a promenade or leisure walkway, it clearly still faces significant deficiencies in pedestrian comfort. This study analyzes the quality of GOS in the corridor through a mixed approach combining field observations, indicator-based quality assessments, and comfort measurements. The results indicate an uneven quality of GOS as part of urban ecology, with strengths in the potential of river landscapes, heritage elements, and pedestrian paths, but weaknesses in vegetation continuity, species diversity, protection from heat and rain, inclusive access, and waste management and plant maintenance. The study recommends low-cost tactical interventions, including the provision of street furniture such as pergolas, pocket parks, and rain gardens, the restructuring of road elements, the strengthening of riparian vegetation, and a community-based collaborative governance model to sustainably improve the quality of GOS. As a riverbank area, it can also strengthen resilience to unpredictable flooding, thereby preserving the area's heritage value.